2020
DOI: 10.1111/nph.16739
|View full text |Cite
|
Sign up to set email alerts
|

Allelic differences of clustered terpene synthases contribute to correlated intraspecific variation of floral and herbivory‐induced volatiles in a wild tobacco

Abstract: Plant volatile emissions can recruit predators of herbivores for indirect defense and attract pollinators to aid in pollination. Although volatiles involved in defense and pollinator attraction are primarily emitted from leaves and flowers, respectively, they will co-evolve if their underlying genetic basis is intrinsically linked, due either to pleiotropy or to genetic linkage. However, direct evidence of co-evolving defense and floral traits is scarce. We characterized intraspecific variation of herbivory-in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(94 reference statements)
1
9
0
Order By: Relevance
“…during the day time (Fig. S1 ), consistent with previous findings [ 27 ]. Because plant volatiles play essential roles in mediating this tri-trophic interaction [ 23 , 26 ] and to get a better understanding of their diurnal/nocturnal regulation, we collected headspace day and night time volatiles from N. attenuata leaves on glasshouse-grown plants elicited by wounding plus M. sexta larval regurgitant (W + R) using PDMS tubing pieces (Kallenbach et al [ 30 ], Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…during the day time (Fig. S1 ), consistent with previous findings [ 27 ]. Because plant volatiles play essential roles in mediating this tri-trophic interaction [ 23 , 26 ] and to get a better understanding of their diurnal/nocturnal regulation, we collected headspace day and night time volatiles from N. attenuata leaves on glasshouse-grown plants elicited by wounding plus M. sexta larval regurgitant (W + R) using PDMS tubing pieces (Kallenbach et al [ 30 ], Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, the same compound is nocturnally released from flowers and attracts adults of the same insect, which provides pollination services [ 24 ]. Further study showed that ( E )-β-ocimene and ( E )-α-bergamotene are correlated with each other across different N. attenuata genotypes, but linalool is independently regulated [ 23 , 27 ]. Furthermore, unlike the emission of linalool, the endogenous leaf pools of conjugates derived from linalool, such as linalool glycosides, lack the diurnal pattern of emissions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a pathway has a limited capacity to generate organ-specific modifications of its end products prior to transport, and the sink organs may lack the metabolic machinery required for such modifications. Other secondary metabolites are locally synthesized, but in this case organ-specific metabolites derived from a shared metabolic pathway may be limited by genetic linkage, through co-localization of genes responsible for modifications within a metabolic pathway, e.g., terpene synthase clusters (Falara et al, 2011;Chen et al, 2020;Xu et al, 2020). Certainly, evolutionary processes may overcome these constraints when there are conflicting selection pressures among organs, as evidenced by the examples above of compounds occurring only in specific organs.…”
Section: Introductionmentioning
confidence: 99%
“…Other secondary metabolites are locally synthesized, but in this case organspecific metabolites derived from a shared metabolic pathway may be limited by genetic linkage, through co-localization of genes responsible for modifications within a metabolic pathway, e.g. terpene synthase clusters (Falara et al, 2011;Chen et al, 2020;Xu et al, 2020). Certainly, evolutionary processes may overcome these constraints when there are conflicting selection pressures among organs, as evidenced by the numerous examples above of compounds occurring only in specific organs.…”
Section: Introductionmentioning
confidence: 99%